Evolutionary criminology and cooperation: retribution, reciprocity, and crime - Svingen, Evelyn (Palgrave's frontiers in criminology theory, 2023)
This book develops an evolutionary theory of crime. Both evolutionary theory and neurocriminology are growing fields that are attracting more and more interest for criminologists and wider fields alike. This book summarises important readings that relate to retribution and punishment and presents some neurocriminological findings. In addition, the book introduces a new methodology for the study of crime: a game theory experiment adapted from the field of behavioural economics. Overall, the book synthesises the key crime literature, presents a new theory of crime in a new field of evolutionary criminology and the methodology to study it, and provides empirical results in support of the theory. For any evolutionary and neuroscientist interested in deviance, this book offers a new model which is testable using more complex methods such as MRI scanners and survival simulations